2021
DOI: 10.7150/ijbs.52619
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Effect of SIRT1 on Extracellular Microenvironment Remodeling

Abstract: The sirtuins family is well known by its unique nicotinamide adenine dinucleotide (NAD +)-dependent deacetylase function. The most-investigated member of the family, Sirtuin 1 (SIRT1), accounts for deacetylating a broad range of transcription factors and coregulators, such as p53, the Forkhead box O (FOXO), and so on. It serves as a pivotal regulator in various intracellular biological processes, including energy metabolism, DNA damage response, genome stability maintenance and tumorigenesis. Although the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 118 publications
1
4
0
1
Order By: Relevance
“…The expression of SIRT1 in oocytes increased in response to mitochondrial dysfunction in pigs and cows [11,12]; however, the level of responsive SIRT1 upregulation was low in oocytes derived from aged cows [12]. These results are consistent with the fact that AGEs inactivate SIRT1/NRF2 pathways [35]. Notably, we found that embryos derived from both aged and MGO-mice had increased SIRT1 expression levels.…”
Section: Discussionsupporting
confidence: 87%
“…The expression of SIRT1 in oocytes increased in response to mitochondrial dysfunction in pigs and cows [11,12]; however, the level of responsive SIRT1 upregulation was low in oocytes derived from aged cows [12]. These results are consistent with the fact that AGEs inactivate SIRT1/NRF2 pathways [35]. Notably, we found that embryos derived from both aged and MGO-mice had increased SIRT1 expression levels.…”
Section: Discussionsupporting
confidence: 87%
“…However, SIRT1 not only affects intracellular homeostasis, but also participates in the remodeling of the extracellular microenvironment ( 101 ). SIRT1 and HIF-1α, as metabolic sensors of redox and oxygen, can modulate both innate and adaptive immune responses through metabolism-dependent and -independent ways ( 102 ).…”
Section: The Association Of Sirt1 With Hypoxia-induced Chemoresistance In Nsclcmentioning
confidence: 99%
“…The yeast Sir2 protein contains a domain comprising approximately 275 amino acid residues that is conserved in Sir2-like proteins found in both prokaryotes and eukaryotes ( Brachmann et al, 1995 ). SIRT1, the most extensively studied and characterized sirtuin, is highly homologous to basic members of the Sir2 family in yeast (32.44 Percent Identity Matrix by Clustal 2.1) ( Wang et al, 2021 ). The human SIRT1 gene, located at 10q21.3 11 , contains a 33,715 bp region, which is highly conserved and comprises nine exons encoding a 747 amino acid protein.…”
Section: Sirt1: Molecular and Functional Featuresmentioning
confidence: 99%